Return Intention Outcomes of Forced Migrants - Byelikova , Yuliya; Taukeer, Mohammed (Border Crossing, 2024)
Why do some forced migrants intend to remain in their new location, while others plan to return? The study is based on in-depth interviews and focus groups with forced migrants from South Asia in Greece in 2017 and collected 423 responses to open-ended questions from Ukrainian refugees in Germany in 2022. Through qualitative analysis and the aspiration-capability theoretical framework, the researchers identified the main return intention outcomes. They added to the analysis two main dimensions of coping with cultural trauma: place (direct or indirect return to origin-country or culture) and time (permanent or temporal). For Ukrainian refugees, return intention outcomes are defined by the image of their country of origin and the temporality of their status. For forced migrants from South Asia, returning intention outcomes are connected to risky and often illegal ways of reaching the EU, their asylum status, and their attempt to recreate their cultural practices in the destination country. Therefore, the findings of the study help develop an understanding of the study of forced migration under the agenda of Sustainable Development Goals (SDGs) 2030 of the United Nations. It would encourage researchers, policymakers and academicians to further research in the area of forced migration and refugees.